PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) DISERTAI MEDIA POWER POINT DALAM PEMBELAJARAN BIOLOGI SISWA KELAS XI MAN SALIDO KABUPATEN PESISIR SELATAN - Pertiwi, Mellya Sandra (Pendidikan Biologi, 2014)
Some teachers of subjects not use various learning models, on the other hand the teacher has not been using a variety of learning media in schools. Students tend to be a lot of silence and fear of being wrong in an opinion or give an answer to the material being taught. Then the teacher does not know the level of student understanding. One alternative to overcome the problems that happen is to implement cooperative learning model number that accompanied the Head Together media power point. This study aims to determine the effect of the application of cooperative learning model NHT with power point slides on learning outcomes of students of class XI MAN Salido South Coastal District of the school year 2014/2015. The research was conducted in the first three feet of the school year 2014/2015. This study is a design experiment with randomized control group posttest-only design. The study population was all students enrolled in the class XI first semester of 2014/2015 academic year spread over 3 classes. With purposive sampling, then the sample were students of class XI IPA2 as a class experiment using learning models NHT type of media with power point and class XI IPA3 as the control class using lecture and question and answer. From the results of experimental studies have shown that the class average (76.70) is higher when compared to the control class (70.10). From the analysis of the data obtained t is 1.89 and price TTable is 1.67. Thus t count> t table which means the research hypothesis H1 is accepted at 95% confidence level (Î± = 0.05) that there is a positive effect of the application of cooperative learning model number head together with media power point.